Career outlook and performance of professional athletes after Achilles tendon rupture: A systematic review - Johns, W.; Walley, K. C.; Seedat, R.; Thordarson, D. B.; Jackson, B.; Gonzalez, T. (Foot & Ankle International, 2020)
Background: The purpose of this systematic review is to examine the literature on Achilles tendon (AT) injuries in professional athletes to determine their rate of return to play (RTP), performance, and career outcome after AT rupture.